Economic comparison : bamboocrete multi-purpose panel and typical reinforced concrete panel - Norhasliya Mohd Daud; Norazman Mohamad Nor; Mohammed Alias Yusof; Muhamad Azani Yahya; Siti Khadijah Che Osmi; Vikneswaran Munikanan; Azrul Affandhi Musthaffa (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study investigated the economic comparison between bamboo reinforced concrete called Bamboocrete with the conventional reinforced concrete panel. Materials contribute significantly to the construction cost. Bamboo can be an alternative to replace steel bars in typical reinforced concrete as it is low in cost and sustainable material. To optimize the benefit, this study used whole solid bamboo as the reinforcement as well as to reduce amount of concrete in the panel, thus reducing the panel weight. Furthermore, the concrete used is lightweight concrete by partially replaced coarse aggregate with Palm Kernel Shell (PKS). The Bamboocrete panel at 1 500 mm height, 300 mm width, and 125 mm thick can sustain axial load of more than 100 KN (10 ton), and flexural bending load between 32.51 to 35.20 kN. Bamboocrete panel contribute towards economical building structures when it is 14% cheaper than steel reinforced concrete. Furthermore, bamboocrete panel is 23% lighter.